Syntheses, Characterization and X-ray Crystal Structure of Trinuclear NiII—NaI—NiII Assembled with Salen-type Schiff Base - Mariama Thiam; Thierno Moussa Seck; Gorgui Awa Seck; Ibrahima Elhadji Thiam; Ousmane Diouf; Pascal Retailleau; Mohamed Gaye (Earthline Journal of Chemical Sciences, 2023)
The present investigation describes the synthesis and structural study of a metal-zinc ligand [NiL].H2O, which was used to generate a trinuclear complex formulated as {Ni(m-L)Na(m-L)Ni}.(SCN)0.6.(Cl)0.4. The title compound crystallizes in the tetragonal space group I41/acd with the following unit cell parameters: a = 185403(5) Å, c = 51.925(2) Å, V = 17849.0(3) Å3, Z = 16, R1 = 0.074 and wR2 = 0.209. Each organic molecule acts as a hexadentate ligand and bridges Ni(II) and Na(I). For both Ni(II) cations the coordination environment around the metal center can be described as distorted square planar. The Na(I) cation is eight coordinated and the polyhedron around the sodium ions is best described as a distorted square anti-prism. The means planes of the two phenyl rings with a methoxy substituent form a dihedral angle of 3.870(4)°, while the dihedral angle values of these mean planes with the means plane of the central phenyl ring are, respectively, 11.233(4)° and 14.138(3)°. The Zn–Na distance is 3.4285(7) Å. Weak hydrogen bonds involving C—H as donor and Cl, S or O as acceptor are observed.